Climate change and Africa - Low, Pak Sum (Cambridge University Press, 2005)
A comprehensive and up-to-date review by the leading experts from a range of disciplines, this book presents issues of most relevance to Africa: disease, energy generation, desertification, drought, sea-level rise, and sustainable development. An invaluable reference for all researchers and policy makers with an interest in climate change and Africa.